Implications of Digitalization of Accounting for the Development of the Accounting Curriculum - Lalu Yayan Ardiansyah; Imtiyaz Farras Mufidah; Anisaul Hasanah (International Journal of Islamic Business and Management Review, 2023)
The rapid increase in digitalization of accounting has changed the business landscape calling for more innovative solutions. At the practitioner level, the use of fintech is a necessity, while at the academic level, fintech has not yet been fully implemented in the learning process. Accounting education must follow the circumstances to be able to produce quality output and be able to compete in the world of work. The aim of this research is to discuss the extent to which accounting digitalization has occurred, what areas are affected by accounting digitalization, the opportunities that arise as a result of accounting digitalization, the readiness of prospective accountants to face accounting digitalization, what changes need to be made to the accounting education curriculum. The method used in research is a qualitative method with the aim of explaining phenomena, attitudes, dynamics that show the actual situation. The data collection process in this research takes the form of observation, interviews, documentation and literature reviews from various written sources related to accounting digitalization. The findings of this research are that there are changes that need to be made by accounting at this time to include artificial intelligence technology such as AI, cloud systems, IoT, into the academic learning process, thereby improving workforce skills in their field when combined with the use of technology. Automation in accounting can reduce the share of work for accounting graduates, causing the demand for workers to decrease, even for technical matters with the help of applications. Digitalization of accounting using cloud computing systems makes it easier for financial decision makers